Image dimensionality change based coding of two-dimensional ``silhouette'' images - Valantinas, Jonas (Lietuvos matematikos rinkinys, 2000)
In this paper we present a new coding scheme for two-dimensional ``silhouette'' images. In order to get higher compression rates, appropriately chosen Hilbert curves are applied to change dimensionality of the images.